Informed consent in Ghana: what do participants really understand?. Issue 1 (21st December 2007) - Hill, Z; Tawiah-Agyemang, C; Odei-Danso, S; Kirkwood, B
Abstract : Objectives: To explore how subjects in a placebo-controlled vitamin A supplementation trial among Ghanaian women aged 15–45 years perceive the trial and whether they know that not all trial capsules are the same, and to identify factors associated with this knowledge. Methods: 60 semistructured interviews and 12 focus groups were conducted to explore subjects' perceptions of the trial. Steps were taken to address areas of low comprehension, including retraining fieldworkers. 1971 trial subjects were randomly selected for a survey measuring their knowledge that not all trial capsules are the same. The subjects' fieldworkers were also interviewed about their characteristics and trial knowledge. Factors associated with knowledge were explored using multi-level modeling. Results: Although subjects knew they were taking part in research, most thought they were receiving an active and beneficial medication. Variables associated with knowledge were education and district of residence. Radio broadcasts benefited those with some schooling. Fieldworkers' characteristics were not associated with subjects' knowledge. Conclusions: Research and debate on new or improved consent procedures are urgently required, particularly for subjects with little education.